2021
DOI: 10.1002/best.202100057
|View full text |Cite
|
Sign up to set email alerts
|

Validierung verteilter faseroptischer Sensorik zur Dehnungsmessung im Betonbau

Abstract: Die Bedeutung von faseroptischen Sensoren hat infolge der verstärkten Strukturüberwachung (Structural Health Monitoring, SHM) von Bauwerken und Bauteilen immens zugenommen [1]. Die verteilte faseroptische Dehnungsmessung auf Basis der Rayleigh‐Streuung ist dabei ein besonders vielversprechendes Verfahren, welches eine hohe Ortsauflösung und Messempfindlichkeit an jedem Punkt der Messfaser bietet, sodass geringste Dehnungsänderungen erfasst werden können [2]. Allerdings fehlen aktuell Qualitätsstandards, die ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Although not explicitly studied in this paper, previous unpublished studies of the authors comparing different adhesives have shown its suitability. For further studies on the matter, the reader is referred to [33,34]. Much research has been carried out to investigate the suitability of various coating types, e.g., [19,23,25].…”
Section: Selection Of Sensing Fibres For Reinforced Concrete Instrume...mentioning
confidence: 99%
“…Although not explicitly studied in this paper, previous unpublished studies of the authors comparing different adhesives have shown its suitability. For further studies on the matter, the reader is referred to [33,34]. Much research has been carried out to investigate the suitability of various coating types, e.g., [19,23,25].…”
Section: Selection Of Sensing Fibres For Reinforced Concrete Instrume...mentioning
confidence: 99%
“…Strains are measured in the core of the optical fiber only and transferred by means of bond from the surrounding material into the DFOS's core, exhibiting strain lag. 25,26 Hence, the (theoretically infinite) strain peak in a crack's location is smeared to both sides of the DFOS. The bond's stiffness is constituted by the materials' parameters, thicknesses and interface interactions of all layers inbetween the surrounding material and the DFOS's core.…”
Section: Transfer Length Of a Crackmentioning
confidence: 99%
“…Strains are measured in the core of the optical fiber only and transferred by means of bond from the surrounding material into the DFOS's core, exhibiting strain lag 25,26 . Hence, the (theoretically infinite) strain peak in a crack's location is smeared to both sides of the DFOS.…”
Section: Automated Data Assessment and Evaluation Workflow Using Dfosmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of various parameters on laboratory scale elements has been studied by many researchers. It has been shown that cyanoacrylate adhesive is suitable for localized bonding of fiber optic cables to the surface of concrete structures due to its low strain loss [3]. However, the concrete surface must be well prepared before the fiber sensors are applied.…”
Section: Introductionmentioning
confidence: 99%